P292 Short tandem repeat genotyping of Indian Candida tropicalis isolates reveals intrahospital cross transmission. (20th September 2022) - Spruijtenburg, Bram; Jain, Kusum; Tarai, Basidhar; Sachdeva, Neelam; Chowdhary, Anuradha; de Groot, Theun; Meis, Jacques
Abstract:  : Poster session 2, September 22, 2022, 12:30 PM - 1:30 PM  : Candida tropicalis is a clinically relevant yeast that causes candidemia in humans with a high mortality rate. The yeast primarily infects immunocompromised patients and causes outbreaks in health care facilities and is the predominant Candida species from clinical specimens in India. Antifungal-resistant isolates have been reported. Here, we applied a novel short tandem repeat (STR) C. tropicalis typing scheme to a collection of 402 clinical and environmental Indian isolates from New Delhi. Multiple large clusters ( n  = 7) containing more than 2 isolates were detected, and allocated to individual hospitals, except for the largest cluster. This cluster contained 14 isolates from two different hospitals, suggesting cross-transmissions. Two closely related clusters are allocated to the same two hospitals. Altogether, a novel high-resolution STR genotyping for C. tropicalis revealed hitherto unrecognized clusters of hospital transmission.